The crisis of a detail as a detail of the crisis - Bagina, Elena (project baikal, 2023)
The birth of a new post-crisis architecture, human-scaled and reflecting deep philosophical and ideological foundations of the society, is possible if these foundations are not destroyed. The crises experienced by architecture in the 20th and early 21st centuries are related to the loss of ideological foundations of the society. The disappearance of symbolic details in architecture is a detail of the general crisis of culture.
Keywords: architecture; symbolic detail; ideological foundation; crisis